Analysis of the Implementation of Sharia Governance and Reputation of the Behavior of Investment on Fintech Sharia - Dewi Putri Mandiri (Jurnal Ilmiah Ekonomi Islam, 2022)
Technological advances have positive impact on the progress in the field of financial system especially in Indonesia. On the other hand, on the financial services in indonesia keeps growing rapidly followed by more sophisticated technology. When this corporation’s financial technology (fintech) in Indonesia is develop rapidly. The high public interest Indonesia use application it makes the technology favorite by users and the use of fintech the higher. High interest of public, behind the development of company financial technology ( fintech ) particularly companies financial technology ( fintech ) about the manner of sharia should it was offset by an obligation implement the principle sharia principle about the manner of sharia governance at each activity This study on the use of quantitative square minimal partial ( pls ) the result is the sharia compliance significantly to behavior have had a positive impact and investment financing providers ( lender ) in syariah fintech peer to peer of lending.